KRITIK AL-JABIRI1 TERHADAP NALAR ARAB ISLAM MENUJU KEBANGKITAN ISLAM - Dewantoro, Mohammad Hajar (Universitas Ahmad Dahlan, 2013)
This study sought to describe the criticism of Al-Jabri Reason stagnation prevailing Salama Islamic Arab and Islamic awakening solutions to epistemology. Expected benefits of this study is to demonstrate the interconnectivity aspect, even unity between fragments in the general conception of Reason Arabic of Islam. The approach used is epistimologi approach (philosophy) associated with science, philosophy of science that concerns the structure which includes ontology, epistemology and axiology. Because the philosophy of science is in Arabic Arabic culture, it would require an additional approach that historical approach. The goal is to discover the fundamental structure of Arabic culture related to the philosophy of science. The conclusion of this study is the study of Islamic Epistemology ala al-Jabri is a paradigm combines Bayani, Irfani and Burhani, who developed dynamically based Rationalism-Burnani toward a future revival of the Islamic world.